2003
DOI: 10.1677/joe.0.1780395
|View full text |Cite
|
Sign up to set email alerts
|

Stereological evaluation of Sertoli cell ontogeny during fetal and neonatal life in two diverse breeds of swine

Abstract: Chinese Meishan (MS) boars have smaller testes due to fewer Sertoli cells compared with White Composite (WC) boars. The objective was to describe Sertoli cell development relative to circulating FSH concentrations in fetal and neonatal MS and WC boars. Testes and blood samples were collected on days 60, 75, 90 and 105 postcoitum (dpc) and 1, 7, 14 and 25 postpartum (dpp). One testis was immunostained for GATA4 or Ki67 antigen to evaluate total and proliferating Sertoli cell numbers respectively. Testicular siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 43 publications
(56 reference statements)
1
19
0
Order By: Relevance
“…The increase of estrogens specifically at weeks 13 and 15 is also paralleled by a corresponding increase of aromatase mRNA expression, whereas the changes of estrogen concentrations and aromatase activity do not reveal an obvious relationship to FSH. Similarly, low FSH concentrations during that period had also been reported by others (Mc Coard et al 2003). The high concentrations of estrogens in umbilical artery plasma during the last trimester are paralleled by a similar course of estrogen concentrations in amniotic fluid (Robertson et al 1985) and in the urine of sows along pregnancy (Velle 1958).…”
Section: Discussionsupporting
confidence: 72%
“…The increase of estrogens specifically at weeks 13 and 15 is also paralleled by a corresponding increase of aromatase mRNA expression, whereas the changes of estrogen concentrations and aromatase activity do not reveal an obvious relationship to FSH. Similarly, low FSH concentrations during that period had also been reported by others (Mc Coard et al 2003). The high concentrations of estrogens in umbilical artery plasma during the last trimester are paralleled by a similar course of estrogen concentrations in amniotic fluid (Robertson et al 1985) and in the urine of sows along pregnancy (Velle 1958).…”
Section: Discussionsupporting
confidence: 72%
“…It has been demonstrated that Sertoli cells provide the environment that protects and nourishes germ cells and supports their development to viable sperm (França and Chiarini-Garcia, 2005) and Sertoli cell proliferation in pigs begins during the prenatal period (McCoard et al, 2002) and continues after birth (Swanlund et al, 1995;França et al, 2000). A critical period of Sertoli cell proliferation occurs during the first 3 weeks after birth (McCoard et al, 2003) and the total number of Sertoli cells achieved will determine testicle size in adulthood, as well as the sperm production capacity (Cooke et al, 1992;Hess et al, 1993). More recently, Flowers (2008) has reported beneficial effects on sperm production for prospective artificial insemination (AI) boars with improved pre-weaning growth, which was achieved by rearing these boars in smaller litters during lactation.…”
Section: Discussionmentioning
confidence: 99%
“…The main determinants of sperm production are Sertoli cells (Sharpe et al, 2003). The most active proliferation of Sertoli cell in pigs begins during the prenatal period and continues for about 30 days postnatal, which ultimately determines the potential for sperm production as an adult (França et al, 2000;McCoard et al, 2002;McCoard et al, 2003). Consequently, it is possible that a boar's potential for sperm production as an adult could be established by the time that it is weaned.…”
Section: Discussionmentioning
confidence: 99%
“…However, Almeida et al (2013) and Smit et al (2013) observed that one-week-old male piglets with low birth weight had lower testes weight and number of Sertoli cells per testis than their heavier counterparts at birth. This suggests that low birth weight may reduce potential for sperm production in adult boars, because the number of Sertoli cells established before puberty determines sperm production as an adult (McCoard et al, 2003). The positive relationship between sperm production in adult boars and their birth weight was confirmed by Estienne & Harper (2010) and Dysart (2014).…”
Section: Introductionmentioning
confidence: 90%